Light Waves and Data Highways: The Physics of Optical Communication Networks - V. Basil Hans (International Journal of Optical Innovations & Research, 2026)
Optical communication has revolutionised modern telecommunication, allowing for the quick transfer of information by light signals. This technology uses optical fibres as the transmission medium and offers higher bandwidth, lower signal loss and faster data transfer than typical electrical communication systems. Optical communication has become a key enabler of internet services, mobile networks, satellite communication and data centers which are all driving the increasing demand for high speed and dependable connectivity. Along with addressing major issues like fibre losses, installation costs, dispersion, and maintenance complexity, the study also explains how optical fibres work and emphasises the significance of light propagation in achieving long-distance communication with minimal loss. This article deals with the principles of optical communication, which covers the generation, transmission and receipt of optical signals. Recent developments in fibre optic technology and their role in supporting next-generation communication systems are also examined, highlighting the growing importance of optical communication in the digital era. It also discusses the advantages, applications, challenges and recent developments in the field of fibre optics technology. It also tackles important issues including dispersion, maintenance complexity, installation costs, and fibre losses. As the demand for worldwide communication keeps on rising, optical communication is a crucial technology that is pushing the future of digital connectivity and information exchange.
Keywords: Data Transferring; Light Waves; Optic fibre; Optical communications; Telecommunications Networks